"Pointsource" Delivery of a Photosensitizer Drug and Singlet Oxygen: Eradication of Glioma Cells In Vitro. (21st April 2014) - Ghogare, Ashwini A.; Rizvi, Imran; Hasan, Tayyaba; Greer, Alexander
Abstract We describe a pointsource sensitizer‐tipped microoptic device for the eradication of glioma U87 cells. The device has a mesoporous fluorinated silica tip which emits singlet oxygen molecules and small quantities of pheophorbide sensitizer for additional production of singlet oxygen in the immediate vicinity. The results show that the device surges in sensitizer release and photokilling with higher rates about midway through the reaction. This was attributed to a self‐amplified autocatalytic reaction where released sensitizer in the extracellular matrix provides positive feedback to assist in the release of additional sensitizer. The photokilling of the glioma cells was analyzed by global toxicity and live/dead assays, where a killing radius around the tip with 0.3 mm precision was achieved. The implication of these results for a new PDT tool of hard‐to‐resect tumors, e.g. in the brain, is discussed.